2020
DOI: 10.3390/ijms21207592
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Endocrine Neoplasia Type 1: The Potential Role of microRNAs in the Management of the Syndrome

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is a rare inherited tumor syndrome, characterized by the development of multiple neuroendocrine tumors (NETs) in a single patient. Major manifestations include primary hyperparathyroidism, gastro-entero-pancreatic neuroendocrine tumors, and pituitary adenomas. In addition to these main NETs, various combinations of more than 20 endocrine and non-endocrine tumors have been described in MEN1 patients. Despite advances in diagnostic techniques and treatment options, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In addition to miR-24, other miRNAs showed to be possibly involved in the MEN1 tumorigenesis or to be deregulated in the sporadic tumor counterparts of the neuroendocrine tissues commonly affected in MEN1 syndrome [ 25 ], and they should be further investigated by functional studies, as was done for miR-24, to assess their importance in MEN1-related tumor development and progression.…”
Section: Future Research Needed In the Field Of Men1 Syndrome And Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to miR-24, other miRNAs showed to be possibly involved in the MEN1 tumorigenesis or to be deregulated in the sporadic tumor counterparts of the neuroendocrine tissues commonly affected in MEN1 syndrome [ 25 ], and they should be further investigated by functional studies, as was done for miR-24, to assess their importance in MEN1-related tumor development and progression.…”
Section: Future Research Needed In the Field Of Men1 Syndrome And Mirnasmentioning
confidence: 99%
“…In the last two decades, tissue-specific altered activity and/or expression of miRNAs have been suggested as possible modulators of MEN1 tumorigenesis [ 22 , 23 , 24 , 25 ], acting synergically with the MEN1 mutation, indicating the miR-24 as a possible effector of tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple endocrine neoplasia type 1 (MEN1) is a rare inherited syndrome characterized by the occurrence of pituitary, parathyroid, and pancreatic tumors in a single patient [ 91 ]. Regarding MEN1-associated PAs, Lines KE et al [ 92 ] studied the levels of three miRNAs, miR-16-1, miR-15a, and let-7a, demonstrated to be downregulated in different subtypes of non-MEN1 PAs [ 16 , 93 , 94 , 95 , 96 , 97 ], in pituitary neoplasms from heterozygous MEN1 mutant mice ( MEN1 +/− mice).…”
Section: Mirnas Deregulated In a Variety Of Pituitary Tumorsmentioning
confidence: 99%
“…Different ncRNAs have several mechanisms of action. In particular, and of interest for this review, miRNAs regulate gene expression by interacting principally with 3′-UTR of mRNA target, by taking it to degradation or by preventing its translation [ 27 ]. LncRNAs can act in various ways, but generally they perform their function by acting as competitive endogenous RNAs (ceRNAs), by binding their miRNA targets and inhibiting the action of the latter [ 21 ].…”
Section: Introductionmentioning
confidence: 99%